“Read and Mark in Holy Scripture”: Reassessing the Scripture Readings of "A Festival of Nine Lessons and Carols" in a Post-Shoah World - Mayfield, Tyler D. (Studies in Christian-Jewish Relations, 2025)
The Christian Eve service, A Festival of Nine Lessons and Carols, broadcast yearly around the world by King’s College, Cambridge, has nine lessons (i.e., biblical passages) read during the service. Today, many churches around the world celebrate the Christmas season by reading these same nine passages: Genesis 3:8-15, 17-19; Genesis 22:15-18; Isaiah 9:2, 6-7; Isaiah 11:1-4a, 6-9; Luke 1:26-35, 38; Luke 2:1, 3-7; Luke 2:8-16; Matthew 2:1-12; John 1:1-14. This article unfolds in three sections as it critically examines the nine biblical lessons to problematize their selection and ordering within this service. First, I place these scripture readings within the literary context of the biblical canon and the liturgical context of the service to understand how these readings weave a particular theological story within the overall service. I focus on how the service frames the lessons liturgically, examining its use of an introductory interpretive sentence at the beginning of each lesson as an exercise in liturgical hermeneutics of the bible. Second, I critique the assumed theology and hermeneutics behind these biblical selections using the theological concept of the Christmas standard canonical narrative and argue that these specific readings in this particular sequence (i.e., the reading of the biblical passages in canonical order from Genesis to Isaiah to the three gospels) are ethically and theologically problematic in a post-Holocaust world. These lessons individually and collectively posit an implicit, problematic theology of the bible as a whole and of the Hebrew Bible/Old Testament in particular, and its understanding of the grand story of Scripture. Third, I suggest new guidelines for selecting lessons and examples for a reimagined service. I explore how Christian leaders might rethink the role of Scripture in this service.